The Impact of Entrepreneurial Behavior and Attitudes in Economic Growth of European Countries - Sofia GOMES1; Pedro FERREIRA1; Tiago TRANCOSO2 (Communications of International Proceedings, 2020)
This article analyzes the impact of entrepreneurial behavior and attitudes on the economic growth of 21 European countries. The objective is through a set of entrepreneurship indicators collected by the Global Entrepreneurship Monitor (GEM) that measure entrepreneurial behaviors and attitudes such as Perceived Opportunities, Perceived Capabilities, Total Early-Stage, Entrepreneurial Activity, Established Business Ownership, Entrepreneurial Employee Activity and Innovation, assess the impact of these indicators of entrepreneurial activity on the economic growth of these countries. The empirical study uses a data panel covering 21 European countries and a period from 2001 to 2019. A statistical analysis of the dependent and independent variables, a correlation analysis, and a multiple linear regression model was estimated. The results suggest that entrepreneurial activity driven by opportunity, innovation, stable business owners and the involvement of employees in promoting entrepreneurial activity has a positive impact on Gross Domestic Product per capita and, as such, stimulates countries' economic growth. Europeans considered in this sample. However, entrepreneurial activity at an early stage and the skills and knowledge to start a new business have a negative impact on the economic growth of these countries. This study complements the existing literature that analyzes the impact of entrepreneurship on economic growth, but using a sample of European countries (there are few empirical studies with this purpose on European countries), and it is innovative since it uses the indicators for the first time. classified as entrepreneurial behaviors and attitudes collected by GEM to assess their impact on countries' economic growth.
Keywords: Entrepreneurial Behavior; Entrepreneurial Attitude; Entrepreneurship; Economic Growth.